The relationship between self-efficacy and problem-solving ability in biology learning at the senior high school - Maulina, Dina; Wijaya, Agung Putra; Viyanti, Viyanti; Wati, Septiana Media; Rakhmawati, Ismi; Ibrahim, Nor Hasniza; Meriza, Nadya (Biosfer: Jurnal Pendidikan Biologi, 2026)
This study aims to examine the relationship between self-efficacy and problem-solving ability in the topic of the human reproductive system at the senior high school level (SMA). The research employed a quantitative correlational design. A total of 65 students were selected using purposive sampling. Data were collected through a self-efficacy questionnaire and an open-ended test to measure problem-solving skills. The data were analyzed using regression analysis, preceded by a Pearson product-moment correlation test at a significance level of α = 0.01, with prerequisite tests applied. The results showed that the self-efficacy of Grade XI students at senior high school in the human reproductive system topic fell within the moderate category as much as 37%, while their problem-solving ability was in the adequate category in 45%. Statistical analysis yielded a significance value (2-tailed) of 0.00<0.01 and a calculated correlation coefficient as much as 0.700> 0.244 this indicates a positive and highly significant relationship between self-efficacy and problem-solving ability, with a strong correlation strength. In conclusion, there was a significant positive relationship between students' self-efficacy and their problem-solving abilities in biology learning, specifically concerning the human reproductive system material.